Marikana : Voices from South Africa's Mining Massacre - Alexander, Peter, 1953 October 29-; Lekgowa, Thapelo; Mmope, Botsang; Sinwell, Luke; Xezwi, Bongani (Book collections on Project MUSE., 2013)
The Marikana Massacre of August 16, 2012, was the single most lethal use of force by South African security forces against civilians since the end of apartheid. Those killed were mineworkers in support of a pay raise. Through a series of interviews conducted with workers who survived the attack, this account documents and examines the controversial shootings in great detail, beginning with a valuable history of the events leading up to the killing of workers, and including eyewitness accounts of the violence and interviews with family members of those who perished.